IL-21/23 axis modulates inflammatory cytokines and RANKL expression in RA CD4+ T cells via p-Akt1 signaling - Bhattacharya, Gargee; Sengupta, Soumya; Jha, Rohila; Shaw, Shubham K.; Jogdand, Gajendra M.; Barik, Prakash K.; Padhan, Prasanta; Parida, Jyoti R.; Devadas, Satish (Frontiers in Immunology, 2023)
Rheumatoid Arthritis is a chronic autoimmune disorder, essentially characterized by joint inflammation and bone degeneration. CD4 + T cells are critically involved in its pathogenesis, mediating inflammation and osteoclastogenesis by RANK-RANKL interaction.Previous studies have shown the role of IL-21 and IL-23 in stabilizing pathogenic Th17 cells; however their involvement in regulating inflammation and RANKL upregulation has not been evinced . In order to delineate the role of IL-21 and IL-23 in RA CD4 + T cells, we neutralized both the cytokines, independently as well as in combination and found a significant downregulation of inflammatory cytokines and RANKL expression. Similar trends were evinced in ex vivo polarised human Th17 cells thus corroborating with our findings in RA patients. Further, we found significant increase in phosphorylation of Akt1 in RA CD4 + T cells. Interestingly, neutralization of IL-21 and/or IL-23 showed downregulation of p-Akt1 and its subsequent inhibition significantly reduced both, inflammatory cytokines and RANKL expression. This identified p-Akt1 as a key phosphoprotein downstream of IL-21/IL-23 axis, responsible for regulating inflammatory cytokines and RANKL expression in RA CD4 + T cells.Altogether, our findings suggest that IL-21/23 axis regulates inflammatory cytokines and RANKL expression through p-Akt in RA CD4 + T cells and ablation of this pathway may ameliorate RA pathogenesis.